Réponses

2014-02-16T15:05:40+01:00
107

pour x = 1 

1³+2 * (1) ² + 3 * 1 + 1 = 4 *1²  + 2*1 -5
1+2-3+1 =4*1 +2 -5
1= 1
donc égalité vraie

pour  x = -2
 (-2) ³ +2*(-2)² - 3* (-2) +1 =4* (-2)²  + 2*(-2) -5 
-8 + 2* 4 -(-6) + 1 = 4 * 4+ (-4) - 5
-8 + 8 -(-6) +1 = 16 +(-4)-5
7= 7
égalité vraie

pour x = 3
3³ + 2*3² - 3*3 +1 = 4*3²+ 2*3 -5
27 + 2* 9 - 9 +1 = 4 * 9 + 6 -5
37 = 41
donc égalité fausse

pour  x = -4
-4³ + 2 *(-4)² + 3*(-4) +1 = 4*(-4)²+2 *(-4) -5
-64 + 2* 16 + (-12) +1=4* 16+ (-8) -5
-43 = 51






2014-02-16T15:11:16+01:00
107 :
a.  x^{3} +2x²-3x+1       4x²+2x-5                
1+2*1²+3*1+1                             4*1+2*1-5
1+2+3+1                                    4+2-5
7                                                1


b.   x^{3} +2x²-3x+1               4x²+2x-5      
 (-2)^{3} +2*(-2)²-3*(-2)+1         4*(-2)² - 4 - 5
-8+8+6+1                                            16-9
7                                                          7

108 :
A = 8* 2^{-2} *32
--------------------------------------
              128

A = (8*(-4)*32) : 128
A = -32*32 : 128
A = -1024  : 128
A = -8* 10^{0}


B = 27*81* 3^{5}
B = 2187* 3^{5}
B = 531441
B= 5.31441* 10^{5}

je t'ai déjà avancer